2010
DOI: 10.1016/j.ijid.2010.08.002
|View full text |Cite
|
Sign up to set email alerts
|

Comparisons of anemia, thrombocytopenia, and neutropenia at initiation of HIV antiretroviral therapy in Africa, Asia, and the Americas

Abstract: Summary Background Hematological abnormalities are common manifestations of advanced HIV-1 infection that could affect the outcomes of highly-active antiretroviral therapy (HAART). Although most HIV-1-infected individuals live in resource-constrained countries, there is little information about the frequency of hematological abnormalities such as anemia, neutropenia, and thrombocytopenia amo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
66
9
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(88 citation statements)
references
References 12 publications
10
66
9
1
Order By: Relevance
“…[6,7] With regard to other studies conducted among South Africans, the prevalence of anaemia among ART-naive patients was similar to that reported by Kerkhoff et al, [10] (~70%), but higher than that documented by Takuva et al [11] and Firnhaber et al, [5] who both reported anaemia (Hb <10 g/dL) in ~20 -25% of patients (as opposed to ~40% with Hb concentrations in this range in our study). The generally higher anaemia prevalence observed in this study compared with the majority of other African cohorts may be attributable to the fact that many of the previous studies in this field were performed in patients who were either enrolled in clinical trials or seen at outpatient ART clinics.…”
Section: Researchsupporting
confidence: 90%
See 2 more Smart Citations
“…[6,7] With regard to other studies conducted among South Africans, the prevalence of anaemia among ART-naive patients was similar to that reported by Kerkhoff et al, [10] (~70%), but higher than that documented by Takuva et al [11] and Firnhaber et al, [5] who both reported anaemia (Hb <10 g/dL) in ~20 -25% of patients (as opposed to ~40% with Hb concentrations in this range in our study). The generally higher anaemia prevalence observed in this study compared with the majority of other African cohorts may be attributable to the fact that many of the previous studies in this field were performed in patients who were either enrolled in clinical trials or seen at outpatient ART clinics.…”
Section: Researchsupporting
confidence: 90%
“…The impact on haematology services is singularly notable because of the numerous haematological complications of HIV infection, which occur secondary to effects of the virus itself, as a result of associated opportunistic infections/malignancies, or as adverse drug effects. [1] Several studies have reported the prevalence of haematological complications in HIV-seropositive patients, [2][3][4][5][6][7] with variables such as disease stage and exposure to antiretroviral therapy (ART) being important determinants. [8] However, there is a paucity of published SA data in this regard, despite the fact that the burden of HIV infection in SA is among the highest in the world.…”
Section: Researchmentioning
confidence: 99%
See 1 more Smart Citation
“…An investigation in South Korea found that the leading risk factor for cytopenia was AIDS status at initial presentation (12). Another study showed that neutropenia was associated with CD4 and platelet counts; and that thrombocytopenia was associated with country, gender, and chronic hepatitis B infection (16). However, studies in India (17) and Rwanda (5) did not find a significant correlation between thrombocytopenia and low CD4 count.…”
Section: Discussionmentioning
confidence: 99%
“…However, some facts should be noted. First, in a recent publication it is mentioned that HIV does not increase the risk of anaemia among the pregnant (2) . This report might be discordant with Finkelstein et al's finding that immunity, specifically CD4 T-cell count, can take a role.…”
Section: Madammentioning
confidence: 99%